TEMPERATURE VARIABILITY AT SENUNU BAY, WEST SUMBAWA - Syamsul Hidayat; Mulia Purba; Jorina Waworuntu (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
The purposes of this study were to determine the variability of temperature and its relation to regional processes in the Senunu Bay. The result showed clear vertical stratifications i.e., mixed layer thickness about 39-119 m with isotherm of 27°C, thermocline layer thickness about 83-204 m with isotherm of 14–26°C, and  the deeper layer from the thermocline lower limit to the sea bottom with isotherm <13°C. Temperature and the thickness of each layers varied with season in which during the Northwest Monsoon the temperature was warmer and the mixed layer was thicker than those during Southeast Monsoon. During Southeast Monsoon, the thermocline layer rose  about 24 m. The 2001, 2006, and 2009 (weak La Nina years),  the Indonesia Throughflow (ITF) carried warmer water, deepening thermocline depth and reducing upwelling strength.  In 2003 and 2008 thickening of mixed layer occurred in transition season  was believed  associated with the  arrival of Kelvin Wave from the west. In 2002 and 2004 (weak El Nino period,) ITF carries colder water shallowing thermocline depth and enhancing upwelling strength. In 2007 was believed to be related with positive IODM where the sea surface temperature were decreasing due to intensification of southeast wind which induced strong upwelling. The temperature spectral density of mixed layer and thermocline was influenced by annual, semi-annual, intra-annual and inter-annual period fluctuations. The cross-correlation between wind and temperature showed significant value in the annual period.  Keywords: temperature, thermocline, variability, ENSO, IODM.